Experience of Architecture - Ar. Kabir Fatema, Dr. Jitendra Singh, Dr. Naresh Garg, Ar. Jayshree Deshpande (International Journal of Advanced Science and Technology, 2020)
Ever since Freudian space; Experience of Architecture has been a point of discussion. WithPhenomenology and especially with Ponty; experiential analysis of Architecture began to bephilosophically explored. With Neuroarchitecture there came a breakthrough in the analysis ofArchitectural experience. Simultaneously many theorists continued to explore the characters thatplayed a role in the experience of architecture. These characters continue to be refined; this paperattempts at understanding the important characters that play a role in the experience of Architecture.Subject (User) and Object (Space) are the most important of characters. Space is further subdividedand explained in the paper. For an experience most vital is interaction between the Space and its User;which is called as Dialogue; Ideas of Dialogue leading to an experience are also elaborated here. Thepaper concludes with an inter-relationship diagram between the characters of Architectural experiencethat can lead into the Experiential Analysis of Architecture; which is the next stage of this research.